2017
DOI: 10.1590/0034-737x201764040014
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial das concentrações de nutrientes foliares da soja correlacionadas com atributos químicos de um Latossolo Vermelho distroférrico

Abstract: Variabilidade espacial das concentrações de nutrientes foliares da soja correlacionadas com atributos químicos de um Latossolo Vermelho distroférrico 1 O estudo dos atributos do solo e da planta, por meio da geoestatística e da consequente geração de mapas de manejo, resulta na utilização racional de fertilizantes e, assim, na redução de custos para o produtor. No ano agrícola de 2013/2014, no município de Selvíria, MS, objetivou-se, com este estudo, avaliar as dependências linear e espacial dos atributos C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
4
0
3
Order By: Relevance
“…The values of N, K, S, B, P, Mg, Zn, Mn, and Fe showed high spatial dependence according to classes set by Dalchiavon & Carvalho (2012), indicating that leaf nutrient contents are not randomly distributed (Table 2). These results agree with those reported by Behera et al (2016), Lima et al (2016), and Gazola et al (2017), who also found spatial dependence of leaf nutrient contents in oil palm, papaya, and soybeans, respectively. From the spatial dependence, it was possible to obtain maps for individual definition of the spatial variability of the nutrients.…”
Section: Spatial Variability Of Leaf Nutrient Contentsupporting
confidence: 93%
“…The values of N, K, S, B, P, Mg, Zn, Mn, and Fe showed high spatial dependence according to classes set by Dalchiavon & Carvalho (2012), indicating that leaf nutrient contents are not randomly distributed (Table 2). These results agree with those reported by Behera et al (2016), Lima et al (2016), and Gazola et al (2017), who also found spatial dependence of leaf nutrient contents in oil palm, papaya, and soybeans, respectively. From the spatial dependence, it was possible to obtain maps for individual definition of the spatial variability of the nutrients.…”
Section: Spatial Variability Of Leaf Nutrient Contentsupporting
confidence: 93%
“…Segundo Cambardella et al (1994, as variáveis classificadas como forte dependência espacial podem ser mais influenciadas por propriedades intrínsecas do solo, ou seja, pelos fatores de formação do solo, enquanto a dependência espacial moderada possivelmente pode estar relacionada com a homogeneização do solo. Além disso, de acordo com Gazola et al (2017), pode-se inferir que devido à alta dependência espacial, o dimensionamento utilizado na malha amostral deste estudo pode ser considerado suficiente para avaliar a variabilidade espacial desses atributos.…”
Section: Resultsunclassified
“…Según Gazola et al (2017) en estudios sobre la variabilidad espacial de las concentraciones de nutrientes foliares de la soya correlacionadas con atributos químicos de un suelo Latosol Rojo con siembra directa, el contenido de magnesio de la capa de 0.01 -0.20 m fue el indicador químico dependiente que presentó el mayor alcance (77.4 m).…”
Section: Resultados Y Discusiónunclassified